(untitled) (Fiep Bulletin - online, 2014)
Despite the acknowledged importance of physical activities and sports as a mean of promoting health, education, inclusion and social integration and development of children and adolescents in the context of public organizations, notes that the sources for the implementation of public policies towards the sport, are still very timid, generating demands that lead volunteers of the local community to develop sport activities without support or knowledge concerning the implications that the misuse of the sport can bring to their lives. Thus, this article presents an assessment on how the sport-educational practices within the actions of the social actors and Supervision of Sports in the Subprefeitura of Ermelino Matarazzo/Ponte Rasa occurred before the implementation of the concept and the "Clube Escola (School Club)" adopted by the Secretariat Hall of Sports, Leisure and Recreation of the City of São Paulo (SEME), Brazil, as well as a proposal for a social empowerment as a model for suggested actions that guarantee individuals access to basic knowledge in physical activities, sports or leisure, to integrate a participatory management, so democratic, inclusive, effective and efficient.